Stable pre-lithiated silicon oxide particles for lithium-ion battery anodes
By heating silicon oxide-based particles with metal to form metal silicide domains and treating them with lithium substances to form composite particles, the capacity loss and cycle life problems of silicon oxide-based particles in lithium-ion battery cells are solved, and efficient battery performance is achieved .
Patent Information
- Application Number
- CN201980014622.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-17
- Filing Date
- 2019-01-18
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-05-13
AI Technical Summary
Silicon oxide-based particles have large capacity losses in the first cycle of lithium-ion battery cells, resulting in low Coulomb efficiency and reduced cell capacity. At the same time, their reaction with water during processing leads to lithium ion loss and anode corrosion.
The metal silicide domain is formed by heating the silicon oxide-based particles with the metal and processed together with the lithium substance to form composite particles including the silicon domain, the lithium silicate domain and the metal silicide domain to reduce initial capacity loss and extend cycle life.
It achieves the maintenance of high capacity and circulation efficiency in lithium-ion battery cells, reduces lithium ion loss and anode corrosion, and extends the cycle life of the battery.
Smart Images

Figure CN112219296B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 619,711 and U.S. Patent Application No. 16 / 250,635, filed on January 19, 2018, which are incorporated herein by reference in their entirety for all purposes. Background of the Invention
[0003] Field of the Invention
[0004] The present invention relates generally to anode active materials for lithium-based battery cells, and more particularly to silicon oxide active materials that have very little capacity loss when used in lithium-ion battery cells.
[0005] Silica-based particles containing both silicon and silicon oxide offer great promise as high-energy anode materials due to their high capacity and good cycling stability. However, this material has a major drawback; its capacity loss in the first cell cycle is large. In a battery cell, during the first lithiation of such silica-based particles, a large amount of silicon oxide reacts irreversibly to form lithium silicate, resulting in low coulombic efficiency in the first cell cycle and an overall reduction in cell capacity.
[0006] It has been shown that some of the silicon oxide in silicon oxide-based particles can be converted to lithium silicate by annealing the particles with a lithium substance before use in a battery anode. However, this conversion often causes at least some crystallization of the silicon, which significantly reduces its cycle life. More importantly, the water widely used for slurry treatment and electrode casting during the manufacture of battery anodes can leach lithium ions from lithium silicate. Therefore, during processing, most of the lithium introduced into the silicon oxide-based particles is leached from the lithium silicate phase into the water, especially near the surface of such particles, and even lost to the anode before the battery can be assembled. Moreover, the leaching of lithium ions into the water increases the pH of the slurry, thereby corroding the silicon and reducing the specific capacity of the anode. As the silicon is etched away, more lithium silicate is exposed, and more leaching occurs, which in turn leads to more silicon etching. This phenomenon is more obvious in silicon oxide-based particles with nano-sized grains, which are particularly useful as anode materials with long cycle life.
[0007] What is needed is a method to modify silica-based particles while maintaining their amorphous state to minimize initial capacity loss and maintain long cycle life when used in battery cell anodes. It would be particularly useful if any such modification was compatible with standard battery cell processing and assembly techniques.
[0008] Overview
[0009] In one embodiment of the present invention, an active material for an anode in a lithium-ion battery cell is disclosed. The active material includes particles containing domains containing silicon; domains containing metal silicides; and domains containing lithium silicate. In one configuration, the metal silicide domains include silicon and a metal selected from chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof. In some embodiments, the particles include a dopant. The dopant may be any one of magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium, and combinations thereof. In one configuration, at least some of the lithium silicate domains include one or more dopants. At least some of the lithium silicate domains at the surface of the particle may have a higher doping concentration than the lithium silicate domains deeper inside the particle. In one configuration, a metal silicide domain is present at at least a portion of the outer surface of the particle. In one configuration, the outer surface does not contain a silicon domain.
[0010] In another embodiment of the present invention, a method for preparing an anode active material comprises the following steps: providing a x particles; adding a metal salt and a reducing agent to the particles; performing a first annealing at a temperature between 500°C and 1000°C in an inert atmosphere for 0.1 to 20 hours; adding an organic liquid containing a lithium substance to the particles; and then performing a second annealing of a second mixture at a temperature between 500°C and 1200°C in an inert atmosphere for 0.1 to 48 hours to form particles containing silicon domains, lithium silicate domains, and metal silicide domains. The metal salt may contain any one of chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof. The lithium substance may contain any one of lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium carbonate, and lithium alcoholate. In one configuration, the lithium substance is a lithium metal particle. In one configuration, the lithium substance is a solution of lithium metal in tetrahydrofuran and polycyclic aromatic hydrocarbons.
[0011] In another embodiment of the present invention, a method for preparing an anode active material comprises the following steps: providing a x The invention relates to a method for preparing a first particle of lithium silicate; mixing the particle with one or more dopants and water; annealing to form a doped first particle; providing one or more lithium species; adding an organic liquid containing a lithium species to the first particle; annealing at a temperature between 500° C. and 1200° C. in an inert atmosphere for 0.1 to 48 hours to form a doped particle containing a silicon domain and a lithium silicate domain. The dopant may contain any one of magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium, and combinations thereof.
[0012] In one configuration, the first annealing includes annealing at a temperature between 500°C and 1000°C in air or an inert gas for 0.1 to 20 hours. In one configuration, the lithium substance is any one of lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium carbonate, and lithium alkoxide, and the first annealing includes annealing at a temperature between 500°C and 1200°C in air or an inert gas for 0.1 to 48 hours. In one configuration, the lithium substance includes lithium metal particles, and the first annealing includes annealing at a temperature between 500°C and 1200°C in an inert gas for 0.1 to 48 hours. In one configuration, the lithium substance is a solution of lithium metal in tetrahydrofuran and polycyclic aromatic hydrocarbons, and the first annealing includes annealing at a temperature between 500°C and 1200°C in an inert gas for 0.1 to 48 hours.
[0013] In another embodiment of the present invention, a negative electrode film is provided. The negative electrode film includes any active material described herein, graphite particles and a binder. In some configurations, the negative electrode film also includes conductive particles. In one configuration, there is a current collector that is electronically connected to the negative electrode film.
[0014] In another embodiment of the present invention, a battery cell is provided. The battery cell comprises a negative electrode film as described above, a positive electrode, and a separator region between the positive electrode and the negative electrode, wherein the positive electrode comprises positive electrode active material particles, conductive particles, and an optional current collector. The negative electrode film, the positive electrode, and the separator further comprise an electrolyte.
[0015] The electrolyte can be any one of LiPF6, LiBF4, LiAsF6, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiCF3SO3, etc. dissolved in propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl propionate (EP), propyl propionate (PP), 1,2-dimethoxyethane (DME), 1,4-dioxane (DOL), tetrahydrofuran (THF), hydrofluoroether (HFE) and combinations thereof.
[0016] The positive electrode active material particles can be any one of lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese cobalt oxide (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium iron phosphate (LFP), lithium cobalt phosphate (LCP), and lithium vanadium phosphate (LVP).
[0017] BRIEF DESCRIPTION OF THE DRAWINGS
[0018]
[0011] The foregoing and other aspects will be readily apparent to those skilled in the art from the following description of illustrative embodiments when read in conjunction with the accompanying drawings.
[0019] Figure 1is a schematic cross-sectional view of a silicon oxide-based particle according to one embodiment of the present invention.
[0020] Figure 2 is a flow chart showing the steps of forming lithium silicate particles according to one embodiment of the present invention.
[0021] Figure 3 is a schematic cross-sectional view of a composite lithium silicate particle having silicon domains and lithium silicate domains according to one embodiment of the present invention.
[0022] Figure 4 is a flow chart showing the steps of forming composite silicate-silicide particles according to one embodiment of the present invention.
[0023] Figure 5 is a schematic cross-sectional view of a composite silicate-silicide particle according to one embodiment of the present invention.
[0024] Figure 6 is a schematic cross-sectional view of a negative electrode according to one embodiment of the present invention.
[0025] Figure 7 is a schematic cross-sectional view of a battery cell according to one embodiment of the present invention.
[0026] Figure 8 Is a graph showing the capacity of a battery cell as a function of cycles.
[0027] Fig. 9 is a graph showing the gases produced as a function of the percentage of copper and aluminum in the pellet.
[0028] Detailed description
[0029] Embodiments of the present invention are illustrated in the context of lithium-ion battery cells.As described herein, the above needs are met by materials and processes in embodiments of the present invention.
[0030] Unless specifically stated otherwise, all ranges disclosed herein are intended to include all ranges subsumed therein. As used herein, "any range subsumed therein" means any range within the stated range.
[0031] As used herein, the term "lithium silicate" can be described by the chemical formula Li2O·zSiO2, where z can be 1 / 4, 1 / 3, 1 / 2, 2 / 3, 1, 2, and 3. It should be understood that lithium silicate often contains various species with different values of x.
[0032] The subscripts "x," "y," "a," and "b" are numbers greater than 0 that represent the molar ratios of the constituent parts of the compound.
[0033] Table I
[0034] Description of terms used in this disclosure
[0035]
[0036] As described herein, silicon oxide-based particles are particles containing both silicon domains and silicon oxide domains. Such silicon oxide-based particles can be pre-lithiated by processing with any of a variety of lithium species to form composite silicate-silicon particles containing both silicon domains and lithium silicate domains. Silicon oxide-based particles can also be processed with other metals to form composite silicided silicon oxide-based particles in which silicon, silicon oxide, and metal silicide domains are present. Silicon oxide-based particles can also be processed to form composite silicate-silicide particles containing silicon, metal silicide, and lithium silicate domains. These particles are described in more detail below.
[0037] In one embodiment of the present invention, silicon oxide-based particles are doped with a multivalent doping element and then pre-lithiated by processing with any of a variety of lithium species to form doped composite lithium silicate particles. This processing has been shown to ensure the stability of the lithium silicate phase in aqueous media (preventing lithium leaching) while maintaining the high capacity and good cycle efficiency of the material and offsetting the capacity loss in the first cycle when used as the active material of the anode in a lithium-ion battery cell.
[0038] In one embodiment of the present invention, silicon oxide-based particles are heated with a metal to convert at least a portion of the silicon on the surface of the particles into a metal silicide, and then processed with any of a variety of lithium species to form composite silicate-silicide particles. Metals that can be used to form silicides include, but are not limited to, chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof.
[0039] Figure 1 FIG. 1 is a schematic cross-sectional view of a silicon oxide-based particle 100 according to one embodiment of the present invention. The particle 100 has silicon oxide (SiO x ) domain 120 (dashed area) and silicon domain 140 (striped area). Figure 1 100 is shown as spherical, but it can have other shapes. Although the particle 100 is shown as having well-defined domains 120, 140, it should be understood that the domains can have any arbitrary shape. In one configuration, silicon oxide (SiO x) domains 120 and silicon domains 140 are not well defined at all, and the particle 100 can be described as a solid solution or fine mixture of silicon oxide and silicon. In one embodiment of the present invention, the particle 100 is approximately equiaxed to an average diameter in the range of 0.1 to 100 μm. In one configuration, the silicon oxide domains 120 account for between 1 wt% and 99 wt% of the particle, and the silicon domains 140 account for the remaining 99 wt% to 1 wt% of the particle. Depending on the conditions used to make the silicon oxide-based particle 100, the size of the silicon oxide domains 120 and the silicon domains 140 can range from less than 1 nm (amorphous) to up to 100 nm (highly crystalline).
[0040] In one embodiment of the present invention, Figure 2 The flowchart of FIG. 1 shows a method for converting silicon oxide-based particles into composite silicate-silicon particles. In step 210, a method is provided as follows: Figure 1 . In step 220, a solution containing lithium is added to the silicon oxide-based particles in an inert atmosphere. The solution can serve as a medium for guiding lithium from a lithium source to the silicon oxide-based particles. The lithium substance in the solution can be any one of lithium hydride, lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium carbonate, lithium alcohol or metallic lithium. The solution can contain polycyclic aromatic hydrocarbons in ether, such as tetrahydrofuran (THF). Examples of useful polycyclic aromatic hydrocarbons include but are not limited to naphthalene, biphenyl, anthracene, phenanthrene, tetracene and pyrene. Other organic solvents that can be used in the solution include but are not limited to diethyl ether (DEE), 1,4-dioxane, dimethoxyethane (dimethyxyethane) and methyl tert-butyl ether. In step 230, the organic solvent is removed from the solution. In step 240, the silicon oxide-based particles are annealed at a temperature between 400° C. and 1000° C. for 0.1 to 48 hours to form composite silicate-silicon particles. For lithium species such as lithium metal and lithium hydride, the annealing in step 240 is performed in an inert gas such as argon.
[0041] Without wishing to be bound by any particular theory, once lithium is introduced into the silicon oxide-based particles, the atomic arrangement within the particles may no longer be uniform. Lithium combines with silicon oxide to form lithium silicate, and any elemental Si remaining from the reaction may form additional silicon domains in the composite silicate-silicon particles. The size of the domains in the composite silicate-silicon particles may be similar to the size of the domains in the silicon oxide-based particles. Larger silicon and lithium silicate domains with higher crystallinity may form at higher processing temperatures, which may adversely affect battery cycle life.
[0042] Figure 3 FIG. 1 is a schematic cross-sectional view of a composite silicate-silicon particle 300 according to one embodiment of the present invention. The particle 300 has a lithium silicate domain 320 and a silicon domain 340. Although the particle 300 is Figure 3 300 is shown as spherical, but it can have other shapes. Although the particle 300 is shown as having well-defined domains 320, 340, it should be understood that the domains can have any arbitrary shape. In one embodiment of the present invention, the particle 300 is approximately isometric with an average diameter in the range of 0.1 to 300 μm. In one configuration, the lithium silicate domains 320 account for between 1wt% and 99wt% of the particle, and the silicon domains 340 account for the remaining 99wt% to 1wt% of the particle. Depending on the conditions used to make the composite silicate-silicon particle 300, the sizes of the lithium silicate domains 320 and the silicon domains 340 can range from less than 1nm (amorphous) to up to 100nm (highly crystalline).
[0043] As described above, when lithium silicate is exposed to water, lithium ions are leached from the lithium silicate and the lithium ions are exchanged with protons in the water, thereby raising the pH of the water. As described above, this leaching of lithium ions from lithium silicate domains can occur when the composite silicate-silicon particles are mixed with water. The increased pH of the water promotes etching of the silicon domains, thereby reducing the amount of silicon active material in the particle. Furthermore, as the silicon domains are etched, additional lithium silicate domains are exposed to water, and the pH of the water is raised even more, accelerating the etching of the silicon domains. This chain reaction can continue until the entire particle is destroyed.
[0044] There are two ways to mitigate this problem: 1) delay the leaching of lithium ions from lithium silicate; 2) delay the etching of silicon.
[0045] Delaying lithium silicate leaching
[0046] In one embodiment of the present invention, lithium silicate in the composite silicate-silicon particles is doped to reduce the leaching of lithium silicate in water. The silicon oxide-based particles are mixed with a dopant and annealed. Examples of useful dopants include, but are not limited to, salts of magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium, and combinations thereof. In one configuration, the silicon oxide-based particles and (one or more) dopants are annealed in air or in an inert gas such as argon at a temperature between 500°C and 1000°C for 0.1 to 20 hours. After doping the silicon oxide-based particles, they can be converted into composite silicate-silicon particles by mixing them with a lithium solution and then annealing them again. In one configuration, this annealing is performed in air or in an inert gas such as argon at a temperature between 500°C and 1000°C for 0.1 to 20 hours.
[0047] In another embodiment of the present invention, the conversion of silicon oxide-based particles to composite lithium silicate particles and the doping of composite lithium silicate particles can be performed using a single anneal. The silicon oxide-based particles are mixed with a lithium solution and (one or more dopants), the organic solvent in the lithium solution is removed, and the mixture is annealed. In one configuration, the annealing is performed at a temperature between 500° C. and 1000° C. in an inert gas such as argon for 0.1 to 48 hours. For all lithium species except lithium metal and lithium hydride, the annealing can be performed in air rather than in an inert atmosphere.
[0048] Prevent silicon etching
[0049] In another embodiment of the present invention, at least a portion of the surface of the silicon oxide-based particles is converted to metal silicide domains, and then, before exposure to water, the particles are lithiated to form composite silicate-silicide particles (containing metal silicide domains, silicon domains, and lithium silicate domains). In one configuration, metal silicide domains mixed with silicon domains and lithium silicate domains are present in the composite silicate-silicide particles. When such composite silicate-silicide particles are exposed to water, lithium ions can still leach from the lithium silicate domains and increase the pH of the water. However, unlike silicon, many metal silicides are extremely resistant to etching. In the case of having metal silicide on at least a portion of the surface of the composite silicate-silicide particles, such composite silicate-silicide particles are only slightly degraded, if at all, during processing in water, and can be used as anode active materials in battery cells.
[0050] exist Figure 4 In one embodiment of the present invention, a method for converting silicon oxide-based particles into composite silicate-silicide particles is shown in the flowchart of FIG. In step 410, a method such as Figure 1 . In step 420, a metal salt and (one or more) carbon precursors are uniformly mixed with the silicon oxide-based particles. Examples of metal salts that can be used include, but are not limited to, nitrates, acetates, lactates, citrates, ascorbates or carbonates of chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium and combinations thereof. In step 430, the silicon oxide-based particles, metal salts and carbon precursors (sugars) are annealed in an inert gas such as argon or nitrogen at a temperature between 500°C and 1000°C for 0.1 to 48 hours to form silicided silicon oxide-based particles, i.e., particles having metal silicide domains, silicon domains and silicon oxide domains. In step 440, a solution containing lithium is added to the silicided silicon oxide-based particles in an inert atmosphere as described above. Details about the solution are included above, reference Figure 2At step 450, the organic solvent is removed. At step 460, the silicide silicon oxide-based particles are annealed at a temperature between 400°C and 1000°C for 0.1 to 48 hours to form composite silicate-silicide particles. For lithium species such as lithium metal and lithium hydride, the annealing at step 460 is performed in an inert gas such as argon.
[0051] Figure 4 The reaction in can be expressed as follows:
[0052] SiO+M→MSi x +Si+SiO2
[0053] Li+SiO2→Li2O·zSiO2
[0054] Figure 5 5 is a schematic cross-sectional view of a composite silicate-silicide particle 500 according to one embodiment of the present invention. Particle 500 has lithium silicate domains 520, silicon domains 540, and metal silicide domains 560. Although particle 500 is Figure 5 500 is shown as a sphere, but it can have other shapes. Although the particle 500 is shown as having well-defined domains 520, 540, 560, it should be understood that the domains can have any arbitrary shape. In one embodiment of the present invention, the particle 500 is approximately equiaxed to an average diameter in the range of 0.1 to 500 μm. In one configuration, the lithium silicate domain 520 accounts for a proportion between 1wt% and 99wt% of the particle, and the silicon domain 540 and the silicide domain 560 together account for the remaining 99wt% to 1wt% of the particle. In one configuration, the size range of the lithium silicate domain 520 is 1nm to 50nm. In one configuration, the size range of the silicon domain 540 is 1nm to 50nm. In some embodiments, the silicon domain 540 is 15nm or less. The size of the domain can be observed by TEM or other imaging techniques. It should be noted that the silicon domain can include multiple smaller-sized silicon grains. In one configuration, the metal silicide domain 560 extends in the particle 500. In one configuration (not shown), metal silicide domains 560 are primarily near the surface of particle 500 and form a network that helps prevent silicon etching during aqueous processing.
[0055] In another embodiment of the invention, the composite silicate-silicide particles are further processed to dope the lithium silicate domains, as described above for the composite silicate-silicon particles.
[0056] In some embodiments, the composite silicate-silicide particles include a dopant selected from magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium and combinations thereof. In some embodiments, the dopant is one of aluminum, magnesium and zirconium. The dopant may be in the lithium silicate domain or in the particle. In some embodiments, the dopant may be primarily near the surface of the particle, or distributed in the particle. In some embodiments, the dopant is primarily near the surface of the particle, and the metal silicide domain is uniformly distributed in the particle.
[0057] According to various embodiments, the particles may be characterized by one or more of the following attributes. First, as described above, in some embodiments, the particles are characterized by comprising a metal silicide (M a Si b ) and lithium silicate (Li2O·xSiO2). In some embodiments, the metal is one or more of copper, manganese and nickel. In some embodiments, the particles have an oxygen:metal (O:M) molar ratio of 10:1 to 25:1, such as 17:1.
[0058] In some embodiments, the particles further include a dopant selected from magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium, and combinations thereof. In some embodiments, the dopant is one of aluminum, magnesium, and zirconium. The particles may be characterized by having a molar ratio of M:dopant of about 1:2 to 5:1. In some embodiments, the ratio is about 2:1.
[0059] As described above, in some embodiments, silicon oxide-based particles are mixed with metal salts to form metal silicides with dopants optionally included. In some embodiments, the relative amounts of M: dopant: SiO can be characterized as: M (e.g., Cu) is 1 to 20%; dopant (e.g., Al) is 0 to 10%; the balance is SiO. In some embodiments, M is 2 to 10%; dopant is 0 to 5%; the balance is SiO. In some embodiments, M is about 2% and dopant is about 1%.
[0060] Battery Cell
[0061] Figure 6 6 is a schematic cross-sectional view showing a negative electrode assembly 600 according to one embodiment of the present invention. The negative electrode assembly 600 has a negative electrode 610 and a current collector 620. The negative electrode 610 includes negative electrode active material particles 615 mixed with an electrolyte 630, such as the above reference Figure 3 and Figure 5Those described. In some configurations, the electrode 600 also contains a small electronic conductive agent (as shown by small gray dots) such as carbon black, carbon nanotubes or conductive graphite. In one configuration, the negative electrode active material particles 615 are held together by a binder such as styrene-butadiene rubber / carboxymethyl cellulose (CMC / SBR) or other advanced binders such as polyacrylic acid or sodium alginate (not shown), and the electrolyte is filled in the space between the negative electrode active material particles 615 and the binder. The negative electrode current collector can be a metal film.
[0062] Figure 7 is a schematic cross-sectional view of a battery cell 700 having a novel negative electrode 710 according to one embodiment of the present invention. Possible configurations and materials of the negative electrode 710 have been described above. Figure 6 The cell 700 also has a positive electrode 760. There is a separator region 770 between the negative electrode 710 and the positive electrode 760. In some configurations, there is a current collector 780 adjacent to the positive electrode 760 and / or a current collector 720 adjacent to the negative electrode 710.
[0063] As known in the art, the positive electrode 760 typically includes positive electrode active material particles, a binder and an electrolyte, and may also contain small electronically conductive particles such as carbon black. In one configuration, the positive electrode active material particles are held together by a binder such as PVDF, and the electrolyte is filled in the space between the positive electrode active material particles and the binder. Examples of positive electrode active materials include, but are not limited to, lithium cobalt oxide, nickel cobalt aluminum oxide, nickel cobalt manganese oxide, and other substances known to those of ordinary skill in the art.
[0064] In an embodiment of the present invention, any one of a variety of lithium-containing compounds can be used as a positive electrode active material. In one embodiment, the positive electrode active material can be in the form of LiMO2, wherein M is a metal, such as LiCoO2, LiNiO2 and LiMnO2. Lithium cobalt oxide (LiCoO2) is a common material for small batteries, but it is also one of the most expensive materials. The cobalt in LiCoO2 can be partially replaced by Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn or Cu. Lithium nickel oxide (LiNiO2) is less prone to thermal runaway than LiCoO2, but it is also expensive. Lithium manganese oxide (LiMnO2) is the cheapest in the conventional material group and has a relatively high power because its three-dimensional crystal structure provides a larger surface area, thereby allowing a larger ion flux between electrodes. Lithium iron phosphate (LiFePO4) is also now commercially used as a positive electrode active material.
[0065] Other examples of positive electrode active materials include: Li(M' X M” Y)O2, where M' and M" are different metals (e.g. Li(Ni X Mn Y )O2、Li(Ni 1 / 2 Mn 1 / 2 )O2、Li(Cr X Mn 1-X )O2、Li(Al X Mn 1-X )O2), Li(Co X M 1-X )O2, where M is a metal, (e.g. Li(Co X Ni 1-X )O2 and Li(Co X Fe 1-X )O2), Li 1-W (Mn X Ni Y Co Z )O2, (e.g. Li(Co X Mn y Ni (1-X-Y) )O2、Li(Mn 1 / 3 Ni 1 / 3 Co 1 / 3 )O2、Li(Mn 1 / 3 Ni 1 / 3 Co 1 / 3-X Mg X )O2、Li(Mn 0.4 Ni 0.4 Co 0.2 )O2、Li(Mn 0.1 Ni 0.1 Co 0.8 )O2), Li 1-W (Mn X Ni X Co 1-2X )O2, Li 1-W (Mn X Ni Y CoAl W )O2, Li 1-W (Ni X Co Y Al Z )O2(such as Li(Ni 0.8 Co 0.15 Al 0.05 )O2), Li 1-W (Ni X Co Y M Z )O2, where M is a metal, Li 1-W (Ni X Mn YM Z )O2, where M is a metal, Li(Ni X-Y Mn Y Cr 2-X )O4, LiM'M"2O4, where M' and M" are different metals (e.g. LiMn 2-Y-Z Ni Y O4、LiMn 2-Y- Z Ni Y Li Z O4、LiMn 1.5 Ni 0.5 O4, LiNiCuO4, LiMn 1-X Al X O4、LiNi 0.5 Ti 0.5 O4、Li 1.05 Al 0.1 Mn 1.85 O 4-Z F Z , Li2MnO3), Li X V Y O Z , such as LiV3O8, LiV2O5 and LiV6O 13 A group of positive electrode active materials can be described as LiMPO4, where M is a metal. Lithium iron phosphate (LiFePO4) is an example of this group. Other examples include LiM X M” 1-X PO4, where M' and M" are different metals, LiFe X M 1-X PO4, where M is a metal (e.g., LiVOPO4 Li3V2(PO4)3), LiMPO4, where M is a metal such as iron or vanadium. Further, the positive electrode may include a metal such as V6O 13 , V2O5, V3O8, MoO3, TiS2, WO2, MoO2 and RuO2 to improve the charge and discharge capacity of the secondary active material. In some configurations, the positive electrode active material includes LiNiVO2.
[0066] The separator region 770 may contain any electrolyte that provides ionic communication between the positive electrode 760 and the negative electrode 710. In various configurations, the separator region 770 contains the same electrolyte as the negative electrode 710 and the positive electrode 760.
[0067] Some examples of non-aqueous solvents suitable for use in certain lithium-ion cells include: cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and vinyl ethylene carbonate (VEC)), lactones (e.g., γ-butyrolactone (GBL), γ-valerolactone (GVL), and α-angelica lactone (AGL)), linear carbonates (e.g., dimethyl carbonate (DMC), ethyl methyl carbonate (MEC), diethyl carbonate (DEC), methylpropyl carbonate (MPC), dipropyl carbonate (DPC), methylbutyl carbonate (NBC), and dibutyl carbonate (DMC). esters (e.g., dibutyl esters (DBC)), ethers (e.g., tetrahydrofuran (THF), 2-methyltetrahydrofuran, 1,4-dioxane, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, and 1,2-dibutoxyethane), nitrites (e.g., acetonitrile and adiponitrile), linear esters (e.g., methyl propionate, methyl pivalate, butyl pivalate, and octyl pivalate), amides (e.g., dimethylformamide), organic phosphates (e.g., trimethyl phosphate and trioctyl phosphate), and organic compounds containing S=O groups (e.g., dimethyl sulfone and divinyl sulfone), and combinations thereof. In some embodiments, a fluorinated ether solvent having the chemical formula RO-R' is used, wherein R and R' are independently C x H 2x+1-y F y , where x and y are integers.
[0068] Non-aqueous liquid solvent can be used in combination.The example of combination comprises the combination of cyclic carbonate-linear carbonate, cyclic carbonate-lactone, cyclic carbonate-lactone-linear carbonate, cyclic carbonate-linear carbonate-lactone, cyclic carbonate-linear carbonate-ether and cyclic carbonate-linear carbonate-linear ester.In one embodiment, cyclic carbonate can be combined with linear ester.And cyclic carbonate can be combined with lactone and linear ester.In a specific embodiment, the ratio of cyclic carbonate and linear ester is about 1:9 to 10:0 by volume, preferably 2:8 to 7:3.
[0069] The salt used for the liquid electrolyte may include one or more of the following: LiPF6, LiBF4, LiCl4, LiAsF6, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiCF3SO3, LiC(CF3SO2)3, LiPF4(CF3)2, LiPF3(C2F5)3, LiPF3(CF3)3, LiPF3(iso-C3Fl)3, LiPFs(iso-C3F1), lithium salts with cyclic alkyl groups (e.g., (CF2)2(SO2) 2x Li and (CF2)3(SO2) 2xLi) and their combinations. Common combinations include LiPF6 and LiBF4, LiPF6 and LiN(CF3SO2)2, LiBF4 and LiN(CF3SO2)2. Example
[0070] The following examples provide details regarding the composition, manufacture and performance characteristics of block copolymer electrolytes according to the present invention. It should be understood that the following are merely representative, and the invention is not limited to the details set forth in these examples.
[0071] Silica-based particles (50 grams) with a Si:O ratio of 1:1 and an average size of 5 μm were mixed with copper acetate equal to 10 wt% Cu and 5 wt% sucrose in 500 mL of deionized water. The suspension was dispersed and dried by a spray dryer to form a precursor. The product with uniformly distributed Cu and sucrose was collected and annealed in argon for 4 hours to form the necessary copper silicide grains. After that, the material was dispersed in 300 mL of anhydrous tetrahydrofuran. Biphenyl (2 grams) was added to the solution, and then 5 grams of polished lithium metal foil was added to the solution. The solution was stirred in a sealed container for 24 hours until all the lithium metal was absorbed by the material. After filtering out the solvent, the material was dried and annealed at 600°C in argon for 2 hours to form composite silicate-silicide particles used as active materials in the anode of the battery cell.
[0072] The composite silicate-silicide particles were mixed in a water-based slurry at a concentration of 9% and used to form the anode. The slurry also contained 1% SBR and 0.8% CMC and 0.1% carbon nanotubes, with the rest being graphite. After coating the slurry on copper foil, the anode was dried and pressed to 1.65 g / cc for battery cell assembly. The battery contained an anode, a polyethylene-based separator, and a lithium cobalt (LCO) cathode. Prior to testing, an electrolyte containing 1.2M LiPF6 in a 3:7EC:DMC solution was added to the battery cell.
[0073] For comparison, a second battery cell was prepared using silicon oxide-based particles that had not yet been converted into composite silicate-silicide particles as an anode active material. As described above, the silicon oxide-based particles had a Si:O ratio of 1:1, and the battery cell was manufactured in the same manner as the composite silicate-silicide particles.
[0074] The battery test procedure included charging at 0.5C rate to 4.4 V, constant voltage to 0.05C and discharging at 0.5C rate to 3 V. The specific capacity delivered per cathode weight (specific capacity) versus the cycle index was used as a benchmark for cell performance. Figure 8Results are shown for an anode made with composite silicate-silicide particles (A) and an anode made with silicon oxide-based particles (B). Both anodes have similar decay slopes, but anode A has a higher capacity.
[0075] As described above, various concentrations of metal (Cu) and dopant (Al) were used to form composite silicate-silicide particles. In particular, the following concentrations were used to form particles:
[0076] Copper only: 2, 10, 15, 5
[0077] Copper / Aluminum: 1 / 2.5, 10 / 1, 10, 5, 2 / 1, 2 / 2, 2 / 2.5, 3 / 1.5, 5 / 2, 5 / 2.5
[0078] The concentrations are given in mole percent, with the remainder being SiO in the starting SiO+Cu+Al mixture. 1 g of each powder was immersed in deionized water for 60 h. The total volume of gas measured at 1 atm after immersion was measured and plotted on Fig. 9 As can be seen, the presence of Al significantly reduces gas generation. This is important; if the material generates gas upon exposure to water, an aqueous slurry for an anode involving the material may contain a large number of bubbles or even become foamy. This can hinder uniform coating of the active material on the current collector.
[0079] The present invention has been described herein in considerable detail in order to provide those skilled in the art with information relating to the application of the novel principles and the construction and use of such specialized components as are required. However, it should be understood that the present invention is capable of being implemented by different means, materials and equipment, and that various modifications both to the means and operating procedures can be accomplished without departing from the scope of the invention itself.
Claims
1. An active material for an anode in a lithium-ion battery cell, comprising: A particle comprising: domains containing silicon; a domain comprising a metal silicide; and domains containing lithium silicate; Each particle has an outer surface, At least some of the lithium silicate-containing domains include one or more dopants.
2. The active material of claim 1, wherein the metal silicide comprises silicon and a metal selected from the group consisting of chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof.
3. The active material of claim 1, wherein the outer surface comprises at least some lithium silicate-containing domains, and at least some of the lithium silicate-containing domains at the surface have a higher doping concentration than lithium silicate-containing domains not at the surface.
4. The active material of claim 3, wherein the dopant is selected from the group consisting of magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium, and combinations thereof.
5. The active material of claim 1, wherein at least a portion of the exterior surface comprises domains comprising a metal silicide.
6. The active material of claim 1, wherein the particles further comprise one or more dopants selected from the group consisting of chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof.
7. The active material of claim 1 wherein the particles are characterized by a molar ratio of oxygen:metal of from 10:1 to 25:
1.
8. A method for preparing an anode active material, comprising: a) Provide SiO x of particles; b) adding a metal salt and a reducing agent to the particles to form a first mixture; c) annealing the first mixture in an inert atmosphere; d) adding an organic liquid containing a lithium species to the particles to form a second mixture; and e) annealing the particles in an inert atmosphere to form particles containing domains containing silicon, domains containing lithium silicate, and domains containing metal silicide.
9. The method of claim 8, wherein the first mixture is annealed at a temperature between 500°C and 1000°C for 0.1 to 20 hours.
10. The method of claim 8, wherein the second mixture is annealed at a temperature between 500°C and 1200°C for 0.1 to 48 hours.
11. The method of claim 8, wherein the metal salt comprises a metal selected from the group consisting of chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof.
12. The method of claim 8, wherein in step d), the lithium species is selected from the group consisting of lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium carbonate and lithium alkoxide.
13. The method of claim 8, wherein in step d), the lithium species is lithium metal particles.
14. The method of claim 8, wherein in step d), the lithium species is a solution of lithium metal in tetrahydrofuran and polycyclic aromatic hydrocarbons.
15. The method of claim 8, further comprising adding a dopant to the first mixture, wherein the dopant is selected from the group consisting of chromium, cobalt, copper, iron, nickel, manganese, titanium, vanadium, and combinations thereof.
16. A method for producing an anode active material, comprising: a) Provide Si and SiO x The first particle of b) mixing the particles with one or more dopants and water to form a first mixture; c) annealing the first mixture to form doped first particles; d) adding an organic liquid containing a lithium species to the first particles to form a second mixture; and e) annealing to form doped particles comprising silicon-containing domains and lithium silicate-containing domains.
17. The method of claim 16, wherein the dopant comprises one or more selected from the group consisting of magnesium, calcium, strontium, barium, boron, aluminum, gallium, indium, thallium, phosphorus, arsenic, antimony, bismuth, titanium, zirconium, hafnium, and combinations thereof.
18. The method of claim 16, wherein in step c), the annealing comprises annealing at a temperature between 500°C and 1000°C for 0.1 to 20 hours in air or an inert gas.
19. The method of claim 16, wherein in step d), the lithium species is selected from lithium hydroxide, lithium nitrate, lithium acetate, lithium oxalate, lithium carbonate and lithium alkoxide, and in step e), the annealing comprises annealing in air or an inert gas at a temperature between 500°C and 1200°C for 0.1 to 48 hours.
20. The method of claim 16, wherein in step d), the lithium species comprises lithium metal particles, and in step e), the annealing comprises annealing at a temperature between 500°C and 1200°C in an inert gas for 0.1 to 48 hours.
21. The method of claim 16, wherein in step d), the lithium species is a solution of lithium metal in tetrahydrofuran and polycyclic aromatic hydrocarbons, and in step e), the annealing comprises annealing in an inert gas at a temperature between 500°C and 1200°C for 0.1 to 48 hours.
22. A negative electrode film comprising a mixture of: Active material particles according to claim 1; Graphite particles; and Adhesive.
23. The negative electrode film of claim 22, wherein the negative electrode film further comprises electronically conductive particles.
24. The negative electrode film of claim 22, further comprising a current collector in electrical communication with the negative electrode film.
25. A battery cell comprising: A negative electrode comprising a particle mixture of the active material according to claim 1, graphite particles, a binder, an optional current collector, and an electrolyte; a positive electrode comprising positive electrode active material particles, electronically conductive particles, an optional current collector, and an electrolyte; In the separator region between the positive electrode and the negative electrode, the separator region contains an electrolyte.
26. The battery cell of claim 25, wherein the electrolyte is selected from LiPF6, LiBF4, LiAsF6, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiCF3SO3 dissolved in propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethyl propionate, propyl propionate, 1,2-dimethoxyethane, 1,4-dioxane, hydrofluoroether and tetrahydrofuran.
27. The battery cell of claim 25, wherein the positive electrode active material particles are selected from the group consisting of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese cobalt oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt phosphate, and lithium vanadium phosphate.
Citation Information
Patent Citations
Composite negative electrode materials
CN102782908A